Peran Manajemen Pengelolaan Kelas Terhadap Minat Beajar Matematika Siswa Sekolah Dasar - Nurul Kamilah; Yayang Furi Furnamasari (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
This study aims to explore the role of classroom management on students' interest in learning mathematics in grade IV at SDN Jelegong 01 Rancaekek. This research was conducted because there were still many students who still had difficulties in solving math problems. This research uses observation method and qualitative approach. Through observing and documenting classroom management practices, this study found that good classroom management has a positive impact on students' interest in learning mathematics. Several important aspects of classroom management that were found included effective time management, the use of effective teaching methods, positive interactions between teachers and students, and creating a conducive classroom atmosphere. The research findings show that these factors can increase students' interest in learning mathematics. Thus, the findings of this study suggest that teachers pay attention to classroom management skills and to vary teaching methods. In this way, students' interest in learning can be increased and the experience of learning mathematics becomes more positive and meaningful for students. The implications of this study emphasize the importance of developing classroom management skills for teachers in increasing students' interest in learning mathematics.